2023
DOI: 10.31067/acusaglik.1340369
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Eating is More Effective to Beat Emotional Eating than Nutrition Education and Diet: A Randomized Controlled Study

İrem İNÖZÜ,
Gizem KÖSE

Abstract: Purpose: Mindful eating have a potential in addressing problematic eating behaviors and focusing the challenges often faced in food consumption. In this study, we conducted a randomized controlled trial that incorporated both mindful eating, including nutritional education with an energy-restricted diet. The aim is to contribute to the literature by revealing the comparative effectiveness of these approaches in alleviating problematic eating behaviors. Methods: This prospective randomized controlled stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…The teachings associated with the practice of mindful eating can be recommended. This has the potential to increase the impact of personalized nutrition plans formulated by dietitians, as well as the effectiveness of nutritional counseling offered to individuals regarding weight management and improving eating habits [ 13 ]. In a study conducted by Miller et al, both mindful eating and diabetes self-management education (DMSE) were found to be effective interventions for enhancing eating regulation and dietary patterns, and reducing symptoms of depression and anxiety in adults with T2DM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The teachings associated with the practice of mindful eating can be recommended. This has the potential to increase the impact of personalized nutrition plans formulated by dietitians, as well as the effectiveness of nutritional counseling offered to individuals regarding weight management and improving eating habits [ 13 ]. In a study conducted by Miller et al, both mindful eating and diabetes self-management education (DMSE) were found to be effective interventions for enhancing eating regulation and dietary patterns, and reducing symptoms of depression and anxiety in adults with T2DM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%